Development and pilot testing of an integrated, web‐based self‐management program for irritable bowel syndrome (IBS). Issue 1 (6th December 2014) - Dorn, S. D.; Palsson, O. S.; Woldeghebriel, M.; Fowler, B.; McCoy, R.; Weinberger, M.; Drossman, D. A.
Abstract Background Although essential, many medical practices are unable to adequately support irritable bowel syndrome (IBS) patient self‐management. Web‐based programs can help overcome these barriers. Methods We developed, assessed, and refined an integrated IBS self‐management program (IBS Self‐care). We then conducted a 12‐week pilot test to assess program utilization, evaluate its association with patients' self‐efficacy and quality of life, and collect qualitative feedback to improve the program. Key Results 40 subjects with generally mild IBS were recruited via the Internet to participate in a 12‐week pilot study. Subjects found the website easy to use (93%) and personally relevant (95%), and 90% would recommend it to a friend. Self‐rated IBS knowledge increased from an average of 47.1 on a 100‐point VAS scale (SD 22.1) at baseline to 77.4 (SD: 12.4) at week 12 (p < 0.0001). There were no significant changes in patient self‐efficacy (Patient Activation Measure) or quality of life (IBS ‐Quality of Life Scale). Conclusions & Inferences The IBS Self‐Care program was well received by users who after 12 weeks reported improved knowledge about IBS, but no significant changes in self‐efficacy or quality of life. If applied to the right population, this low cost solution can overcome some of the deficiencies of medical care and empower individuals to better manage their own IBS.